2018
DOI: 10.1049/iet-nbt.2018.5212
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ZnO nanoparticles on proline, anthocyanin contents and photosynthetic pigments and lipid peroxidation in the soybean

Abstract: The interaction between nanoparticles and plants is inevitable. In this study, the effect of different concentrations of ZnO nanoparticles synthesised using olive extract on the soybean was studied. The soybean seeds were cultured in a Hoagland medium containing agar which was treated different concentrations (0, 200 and 400 ppm) of ZnO nanoparticles. After 21 days, the plants were harvested and the parameters of proline, anthocyanin, malondialdehyde (MDA), hydrogen peroxide (H 2 O 2), chlorophyll and caroteno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 56 publications
4
6
1
Order By: Relevance
“…Foliar application of ZnO NPs at low concentrations enhanced the anthocyanin content in the berries' skin. Our results were consistent with Song et al [21], who mentioned that Zn treatments enhanced the accumulation of anthocyanins in berry skin, and Hashemi et al [56], who explained the role of ZnO nanoparticles in increasing anthocyanin production in soybean. Additionally, Wadhwa et al [51] mentioned that Zn served as a co-factor for PAL enzyme activity and Medda et al [12] advocated that Zn played a regulatory enzyme during fruit ripening for flavonoid biosynthesis.…”
Section: Discussionsupporting
confidence: 93%
“…Foliar application of ZnO NPs at low concentrations enhanced the anthocyanin content in the berries' skin. Our results were consistent with Song et al [21], who mentioned that Zn treatments enhanced the accumulation of anthocyanins in berry skin, and Hashemi et al [56], who explained the role of ZnO nanoparticles in increasing anthocyanin production in soybean. Additionally, Wadhwa et al [51] mentioned that Zn served as a co-factor for PAL enzyme activity and Medda et al [12] advocated that Zn played a regulatory enzyme during fruit ripening for flavonoid biosynthesis.…”
Section: Discussionsupporting
confidence: 93%
“…An increase of chlorophyll content improves the efficiency of photosynthesis, which can increase plant biomass and yielding. The obtained results confirm the research conducted by Neshev and Manolov (2015), who observed an increase of chlorophyll a and b content during conventional fertilisation [36]. The influence of nanoparticles on chlorophyll a and b production was tested by Dimkpa et al (2017) [31].…”
Section: Chlorophyll a I Bsupporting
confidence: 89%
“…In this case, the reduction of MDA compared to control samples ( Figure 7 ) may result from the activation of other protective and antioxidant mechanisms due to the severe impact of this treatment. This can be due to the onset of severe oxidative stress as it was found for maize treated with NPs at 800 µg L −1 [ 51 ] and soybean exposed to ZnO-NPs at 200 and 400 µg L −1 [ 64 ]. Likewise, T200 started to show some adverse effects on the various parameters studied compared to the other dosages.…”
Section: Discussionmentioning
confidence: 99%